Cottoperca trigloides, Frogmouth - Buratti, C. (2020)
This widely distributed, demersal species is associated with rocky bottoms and kelp forests. It is discarded as bycatch in trawl fisheries, but this is not expected to be driving population declines approaching a Near Threatened or threatened level at this time; therefore, it is listed as Least Concern.